Hyperglycemia-independent neonatal streptozotocin-induced retinopathy (NSIR) in rats - Lin, Yu; Du, Wenyu; Fu, Xiangyu; Huang, Ling; Hong, Yiwen; Tan, Haishan; Xiao, Lirong; Ren, Xiang; Wang, Yujiao; Chen, Danian (Frontiers in Pharmacology, 2024)
Chemicals, such as MNU (N-methyl-N-nitrosourea) and NaIO3 (sodium iodate), are widely used to induce retinal degeneration in rodents. Streptozotocin (STZ) is an analog of N-acetyl glucosamine in which an MNU moiety is linked to a hexose and has a special toxic effect on insulin-producing pancreatic β-cells. It is commonly used to induce hyperglycemia to model diabetes. While intracerebroventricular injection of STZ can produce Alzheimer's disease independent of hyperglycemia, most retinal studies using STZ focus on the effects of hyperglycemia on the retina, but whether STZ has any impact on retinal cells independent of hyperglycemia is unknown. We aimed to investigate the role of cytotoxicity of STZ in rat retina. Intravitreal (5g or 10g) or subcutaneous (30mg/kg) injection of STZ at the early stage of newborn rats couldn't induce hyperglycemia but caused NSIR (neonatal STZ-induced retinopathy), including reduced ERG amplitudes, retinal rosettes and apoptosis, cell cycle arrest, microglial activation, and delayed retinal angiogenesis. STZ did not affect the early-born retinal cell types but significantly reduced the late-born ones. Short-term and long-term hyperglycemia had no significant effects on the NSIR phenotypes. RNA sequencing revealed that STZ induces oxidative stress and activates the p53 pathway of retinal cells.Locally or systemically, STZ injection after P8 couldn't induce NSIR when all retinal progenitors exit the cell cycle. Thus, NSIR in rats is independent of hyperglycemia but due to STZ's direct cytotoxic effects on retinal progenitor cells. NSIR is a typical reaction to STZ-induced retinal oxidative stress and DNA damage. This significant finding suggests that NSIR may be a valuable model for studying retinal progenitor DNA damage-related diseases, potentially leading to new insights and treatments.